2016
DOI: 10.3727/152599516x14682560744794
|View full text |Cite
|
Sign up to set email alerts
|

Community Engagement and Public Events: The Case of Australian Folk Festivals

Abstract: The impact of public events on their host communities has been an area of increasing researcher focus over the past decade. While acknowledging this, little effort has been directed at identifying those practices purposefully employed by the organizers of such events for community engagement purposes. This exploratory study, undertaken in the Australian context, seeks to go some way towards addressing this gap in the literature by examining one type of public event—folk festivals—which anecdotally have a repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Many have demonstrated that place-based community events can play an active role in facilitating positive outcomes such as enhancing place identities, enabling intercultural encounters, building social capital and improving individual subjective well-being (Andrews and Leopold, 2013; Hassanli et al ., 2020, 2021; Jaeger and Mykletun, 2013; Jepson and Clarke, 2015a, b; Piazzi and Harris, 2016). However, events cannot address all the challenges faced by neighbourhoods or communities, especially those that are super-diverse and complex.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Many have demonstrated that place-based community events can play an active role in facilitating positive outcomes such as enhancing place identities, enabling intercultural encounters, building social capital and improving individual subjective well-being (Andrews and Leopold, 2013; Hassanli et al ., 2020, 2021; Jaeger and Mykletun, 2013; Jepson and Clarke, 2015a, b; Piazzi and Harris, 2016). However, events cannot address all the challenges faced by neighbourhoods or communities, especially those that are super-diverse and complex.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This study shifts the focus of economic value creation in events away from the major cities that are prevalent in the literature. Previously, the study of towns and smaller cities has been mainly limited to a case study approach (Moscardo, 2007;Piazzi & Harris, 2016). For example, Alves, Cerro, & Martins, (2010) demonstrated the importance and impacts of small rural tourism events and Fountain & Mackay, (2017) describe the role of a rural festival in placemaking for the small town of Akaroa in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…These are especially important for rural events to take shape because there is not always ample or adequate supply across certain areas which might be taken-for-granted in cities (Ziakas & Boukas, 2016). Understanding all these aspects is something that challenges event managers in rural communities, because local residents tend to be deeply involved in the event organisation (Đurkin & Wise, 2018;Perić et al, 2016;Piazzi & Harris, 2016). Compared to major events, smaller events in rural areas may appear manageable given they do not require large investments, new infrastructures or involve complex relationships across different governance levels (Alves et al, 2010;Gibson et al, 2012).…”
mentioning
confidence: 99%